2022
DOI: 10.3389/fimmu.2022.745997
|View full text |Cite
|
Sign up to set email alerts
|

Natural Compounds Tapinarof and Galactomyces Ferment Filtrate Downregulate IL-33 Expression via the AHR/IL-37 Axis in Human Keratinocytes

Abstract: Interleukin (IL)-37 suppresses systemic and local inflammation. It is expressed in the epidermis, the external layer of the skin, and is decreased in inflammatory skin diseases including atopic dermatitis (AD) and psoriasis. Therefore, an agent applied topically on the skin that can increase IL-37 could be promising for treating AD and psoriasis; however, the mechanism regulating IL-37 remains largely unknown. Given that IL-37 expression is induced in differentiated keratinocytes, a major component of the epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…This is a potential therapeutic approach for psoriasis. [ 78 , 79 ]. In May 2022, tapinarof was approved by the FDA for psoriasis treatment as a topical cream following successful clinical trials that confirmed its effectiveness [ 94 , 95 ].…”
Section: Potential Therapeutic Targets and Signaling Pathways For Pso...mentioning
confidence: 99%
“…This is a potential therapeutic approach for psoriasis. [ 78 , 79 ]. In May 2022, tapinarof was approved by the FDA for psoriasis treatment as a topical cream following successful clinical trials that confirmed its effectiveness [ 94 , 95 ].…”
Section: Potential Therapeutic Targets and Signaling Pathways For Pso...mentioning
confidence: 99%
“…Notably, GFF upregulated IL-37 expression in human keratinocytes in an AHR-dependent fashion [ 116 ] ( Figure 2 ). The GFF-induced IL-37 is biologically active, because it downregulates the expression of IL-33 in keratinocytes [ 116 ].…”
Section: Increased Production Of Antiinflammatory Cytokine Il-37 By Gffmentioning
confidence: 99%
“…Notably, GFF upregulated IL-37 expression in human keratinocytes in an AHR-dependent fashion [ 116 ] ( Figure 2 ). The GFF-induced IL-37 is biologically active, because it downregulates the expression of IL-33 in keratinocytes [ 116 ]. Moreover, the GFF-AHR-IL-37-induced downregulation of IL-33 is canceled by the knockdown of either AHR or IL-37 [ 116 ].…”
Section: Increased Production Of Antiinflammatory Cytokine Il-37 By Gffmentioning
confidence: 99%
See 2 more Smart Citations